Baer in Posthemorrhagic Ventricular Dilatation - J Gordon Millichap (Pediatric Neurology Briefs)
Nineteen infants with pos themorrhagi c ventricular dilatation were studied with serial auditory brainstem responses at the Department of Paediatrics and Neonatal Medicine, Hammersmith Hospital, London.